2008
DOI: 10.1007/s10165-008-0105-5
|View full text |Cite
|
Sign up to set email alerts
|

Remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome following spontaneous rupture of a gouty tophus

Abstract: A 70-year-old man with a 30-year history of gout presented with a ruptured gouty tophus over the right lateral malleolus. After the debridement of the tophus, bilateral arthralgia and pitting edema were observed in his extremities. Treatments with antibiotics and nonsteroidal antiinflammatory drugs were ineffective. However, prednisolone therapy was highly effective, and the patient's symptoms were rapidly ameliorated. Thus, we presume that rupture of a gouty tophus or its surgical treatment might contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These rheumatic conditions are systemic lupus erythematosus [40], gout [41], Sjogren's syndrome [42], polyarteritis nodosa [43], ankylosing spondylitis [44], sarcoidosis [45], amyloidosis [46], relapsing polychondritis [27], and bronchiolitis obliterans organizing pneumonia [47]. In addition, other medical conditions or drugs associated with RS3PE include diabetes mellitus [48], dipeptidyl peptidase-4 inhibitors [49], rifampin [50], and insulin therapy [51].…”
Section: Rs3pe Is Associated With Diseases and Medications Other Thanmentioning
confidence: 99%
“…These rheumatic conditions are systemic lupus erythematosus [40], gout [41], Sjogren's syndrome [42], polyarteritis nodosa [43], ankylosing spondylitis [44], sarcoidosis [45], amyloidosis [46], relapsing polychondritis [27], and bronchiolitis obliterans organizing pneumonia [47]. In addition, other medical conditions or drugs associated with RS3PE include diabetes mellitus [48], dipeptidyl peptidase-4 inhibitors [49], rifampin [50], and insulin therapy [51].…”
Section: Rs3pe Is Associated With Diseases and Medications Other Thanmentioning
confidence: 99%
“…[23] Sugisaki and Hirose reported another gout-associated RS3PE syndrome case in which NSAID treatment exerted no therapeutic effect and was finally successfully treated with low-dose oral prednisolone. [24] Recent studies have demonstrated the association of RS3PE with antidiabetic drugs such as insulin and dipeptidyl peptidase-4 (DPP-4) inhibitör Yamauchi et al reported two Japanese cases of RS3PE syndrome, which arose after the onset of DPP4 treatment. [25,26] Yokota and Igaki reported a case of polyarthritis developing after the initiation of sitagliptin, diagnosed with RA, and whose arthritis improved after the withdrawal of sitagliptin.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutional symptoms including fever, malaise, fatigue and weight loss can be seen. Although the name includes the term synovitis, the most characteristic finding is tenosynovitis of the extensor tendons of the hands, RS3PE has been described in association with other rheumatologic disease including sarcoidosis [3], gout [4], Sjogren syndrome [5] and polymyalgia rheumatica [6,7].…”
Section: Discussionmentioning
confidence: 99%